A new nitrogen rich porous organic polymer for ultra-high CO2 uptake and as an excellent organocatalyst for CO2 fixation reactions - Chowdhury, Avik; Bhattacharjee, Sudip; Chatterjee, Rupak; Bhaumik, Asim (Journal of CO2 utilization, 2022)
The steady increase in the carbon dioxide (CO2) concentration in the atmosphere is causing serious environmental threats like global warming and climate change. Thus to mitigate this issue, suitable adsorbent cum catalyst for high CO2 capture and its fixation to reactive organics is very much essential. In this context, we have synthesized a new porous cross-linked organic polymer DAT-1 through the radical polymerization of divinylbenzene, triallylamine and 2,4,6-tris(allyloxy)− 1,3,5-triazine. DAT-1 possesses high degree of flexibility, with exceptionally large BET surface area (1105 m2g−1) along with bimodal porosity. Furthermore, due to the presence of triazine unit along with tertiary amine moieties inside the porous architecture of DAT-1 with very rich in basic N-sites could make it as an excellent adsorbent for the unprecedented CO2 capture (73.3 mmol g−1 at 30 bar pressure / 273 K). Further, it exhibits excellent catalytic activity for the conversion of simple terminal epoxides to bio-derived sterically hindered epoxides to cyclic carbonate by utilizing carbon dioxide as C1 resource. Basicity associated with N-rich sites at the surface of the high surface area porous organic polymer is responsible for record CO2 capture and its excellent catalytic activity for the CO2 fixation on epoxides for the synthesis of value added cyclic carbonates. [Display omitted] •A new porous organic polymer DAT-1 has been synthesized through the polymerization of three olefines.•DAT-1 possesses exceptionally large BET surface area (1105 m2g−1) along with bimodal porosity.•DAT-1 displayed unprecedented CO2 capture (73.3 mmol g−1 at 30 bar pressure / 273 K).•DAT-1 showed excellent catalytic activity for the synthesis of cyclic carbonates via cycloaddition of CO2 on epoxides.•Basicity due to N-rich sites and high surface area are responsible for record CO2 capture and high catalytic activity.